2015
DOI: 10.1159/000440653
|View full text |Cite
|
Sign up to set email alerts
|

Galactose-α-1,3-Galactose Allergy Is Not a Hitherto Unrecognized Cause of Chronic Spontaneous Urticaria

Abstract: Background: Tick bite-induced galactose-α-1,3-galactose (α-Gal) IgE and subsequent ingestion of red meat may cause delayed severe allergic reactions including urticaria, gastrointestinal symptoms or anaphylaxis. We tested the hypothesis that increased levels of IgE to α-Gal due to tick bites and the subsequent ingestion of red meat or meat products may possibly be an un(der)recognized cause of chronic spontaneous urticaria (CSU). Methods: Levels of IgE to α-Gal and total IgE were measured (ImmunoCAP, Phadia AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Taken together the name ‘α-gal syndrome’ seems an appropriate descriptor. Although anecdotally we have seen a few cases of chronic urticaria in α-gal patients on full avoidance diets, a recent report from Sweden did not substantiate a link [26]. …”
Section: Red Meat Allergy and Morementioning
confidence: 98%
“…Taken together the name ‘α-gal syndrome’ seems an appropriate descriptor. Although anecdotally we have seen a few cases of chronic urticaria in α-gal patients on full avoidance diets, a recent report from Sweden did not substantiate a link [26]. …”
Section: Red Meat Allergy and Morementioning
confidence: 98%
“…Maurer et al. 7 reported a prevalence of α‐gal sensitization of 2.4% in 83 patients with CU and no association between ingestion of red meat and development of subsequent delayed urticaria symptoms. In contrast, Pollack et al.…”
Section: Tablementioning
confidence: 99%
“…Maurer et al 7 reported a prevalence of α-gal sensitization of 2.4% in 83 patients with CU and no association between ingestion of red meat and development of subsequent delayed urticaria symptoms. In contrast, Pollack et al 8 found that 9 (60%) of 15 α-gal sensitized CU patients had remission of urticaria symptoms due to avoidance of red meat or other mammalian-derived food products.…”
mentioning
confidence: 99%
“…Pollack et al noted remission of symptoms in such patients on avoiding mammalian meat 16 . In contrast Maurer et al reported the absence of urticarial symptoms, even when patients with detectable levels of anti‐α‐gal IgE consumed red meat 17 Elimination of fish and fish products …”
Section: Elimination Dietsmentioning
confidence: 99%
“…Dietary elimination of fish or fish products and mammalian meat or meat products has Grade B recommendation each, while dietary elimination of gluten has Grade C recommendation (Table 3 ) 16,17,19–22,24–41 . However, elimination diets may be tried in a subset of refractory CSU patients, for example, those with a history of anaphylaxis, resident of tick endemic areas for AGS, or confirmed coexistence of food allergy by a double‐blind placebo‐controlled food challenge, when benefits outweigh risks.…”
Section: Elimination Dietsmentioning
confidence: 99%